Electrochemical formation of anodic oxide films on Nb surfaces: ellipsometric and Raman spectroscopical studies - Arsova, Irena; Arsov, Ljubomir; Hebestreit, Niels; Anders, Andreas; Plieth, Waldfried (SPRINGER, 2007)
Electrochemical formation of anodic oxide films on niobium (Nb) surfaces in 1 M H2SO4 solutions was studied using ellipsometry and Raman spectroscopy. By in situ ellipsometric measurements, the coefficient of film thickness growth and the complex index of refraction of anodic oxide films in the voltage range between 0 and 100 V were determined. The Raman spectra reveal that the thin passive films are amorphous. In the beginning of crystallization, the anodic oxide films consist of mixtures of NbO2 and Nb2O5, while NbO2 is completely transformed to Nb2O5 for thicker and well-crystallized films.